EVALUATING FARROWING REARING AMBIENT USING SOWS’ VOCALIZATION - TOLON, Yamilia Barrios; BARACHO, Marta dos Santos; NÄÄS, Irenilza de Alencar; CALDARA, Fabiana Ribeiro; GARCIA, Rodrigo Garófallo; SILVA, Wagner T. (Revista Brasileira de Engenharia de Biossistemas, 2013)
The analysis of sound signals is shown as a good indicator to estimate animals’ welfare. The analysis of animal vocalization allows access to non-invasive estimation to the state and condition of the animals. This study aimed to assess the housing conditions of farrowing sows using the record of the sound environment where sows were housed. The analysis of the acoustic environment consisted of two parts the interpretation of the noise level and the understanding of the animals’ vocalization and its association with stress. A software was developed in order to analyze the signals using neural networks. For the network training two sows in individual stalls and one sow in a group housing were randomly selected, and a microphone was connected to a computer to record and process the waveforms of the sounds emitted by the sow during lactation, and its corresponding spectrum frequency. From the results it was not possible to state that the rearing environment has caused significant changes in the frequencies of vocalizations of the animals. However, a slight tendency toward higher frequency peaks in the individual installation was found, indicating the presence of stress.